1967
DOI: 10.1002/polc.5070160342
|View full text |Cite
|
Sign up to set email alerts
|

Laws of mechanical relaxation processes in polymers

Abstract: Certain distinctive characteristics of relaxation processes in polymers due to a chain structure of macromolecules and supermolecular structure of a polymeric body call for a new approach to their quantitative description. A mathematical method of description of relaxation processes based on the use of fractional integral operators is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Viscoelastic models based on fractional derivatives (FD) were introduced by Sloninsky in 1967 [25] to find a parsimonious representation for complex media. The mechanical responses predicted by such models were found to be consistent with the molecular theory of polymers by Bagley and Torvik [26].…”
Section: Introductionmentioning
confidence: 99%
“…Viscoelastic models based on fractional derivatives (FD) were introduced by Sloninsky in 1967 [25] to find a parsimonious representation for complex media. The mechanical responses predicted by such models were found to be consistent with the molecular theory of polymers by Bagley and Torvik [26].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand Nutting (1921) observed that the creep or the relaxation test performed on any real material follow a power law kernel instead of an exponential one. Based on this observation the constitutive law of any real material, including rubber, glass, asphalt mixture, is ruled by a fractional operator (Koeller 1984;Bagley, Torvik 1983, 1986Slonimsky 1967;Smit, de Vrie 1970;Soczkiewicz 2002;Di Paola et al 2011). The characterization of the real material by means of fractional derivative and integrals of real order produces strong variations on the response with respect to the characterization involving derivatives (or integrals) of integer order.…”
Section: Introductionmentioning
confidence: 99%
“…(1.1) can be obtained from a fractional vibration equation for viscoelastic damped structures with a springpot component. The springpot, also known as the Scott Blair element, is an intermediate body between the purely elastic (Hookean element) and the perfectly viscous liquid (Newtonian element), see [32,33]. In 1967, Slonimsky [32] introduced the viscous element in studying the laws of mechanical relaxation processes in polymers.…”
Section: Introductionmentioning
confidence: 99%